Preparation of twin graphene quantum dots through the electric-field-assisted femtosecond laser ablation of graphene dispersions. (15th November 2021) - Li, Xiaojie; Li, Xin; Jiang, Lan; Zuo, Pei; Zhao, Yang; Wang, Sumei; Chen, Xiaozhe; Liang, Misheng; Ma, Le
Abstract: Twin graphene can introduce stable and extended defects to energy band engineering, giving unique electron transport properties, which is expected to have potential applications in the fields of magnetism, spin transport or photoluminescence. This study proposes a method of using electric-field-assisted temporally-shaped femtosecond laser ablation liquid (ETLAL) of graphene dispersion to prepare graphene quantum dots (GQDs) with an average particle size of 2–3 nm and oxygen-containing functional groups modified surface, which realizes the controllable preparation of single crystal and twin GQDs (5-fold twin). This method controls the crystallinity of GQDs from two aspects: (1) The intervention of an electric field can rapidly command the directional motion of the cavitation bubbles and the nanoparticles contained therein to collide and crystallize at higher temperatures and pressures, which is the key to the formation of twin GQD; (2) Adjusting temporally-shaped femtosecond laser pulse delay could control the proportion of the Coulomb explosion during the ablation process, which increases the carbon cluster supplied by the cavitation bubble which is the key of polyploid number in twin GQDs. This research provides a fast, green strategy for the preparation of unprecedented twin GQDs, which is of great significance to the applications in the field of 2D material defect engineering. Graphical abstract: Image 1